MiR-34a and miR-29b as indicators for prognosis of treatment-free survival of chronic lymphocytic leukemia patients in Chinese Uygur and Han populations. (October 2019) - Li, Yan; Mao, Min; Liu, Hong; Wang, Xiaomin; Kou, Zhen; Nie, Yuling; Wang, Yichun; Wang, Zengsheng; Huang, Qin; Lang, Tao; Gu, Zailinuer; An, Li; et al.
Abstract: The abnormal expression of miRNAs may play critical roles in the occurrence, development and prognosis of chronic lymphocytic leukemia (CLL), with potential ethnic differences being involved. p53 and immunoglobulin heavy chain variable region gene (IGVH) mutations were monitored and miRNA profile screening of CD19  +  cells from Uygur CLL patients was performed, analyzed by miRNA arrays and verified using real-time PCR. There were 68 differentially expressed miRNAs in CD19  +  B lymphocytes obtained from 6 Uygur CLL patients, of which miR-1295, miR-29b, miR-34a, miR-21 and miR-29c were the 5 most upregulated, and miR-181a, miR-126, miR-181b, miR-125a-5p and miR199b the 5 most downregulated miRNAs. miR-15a/miR-16-1 which might be important drivers of the disease, were not eliminated by profile screening. From the 68 differentially expressed miRNAs, 5 previously-reported CLL-related miRNAs were selected for further confirmation analyses, from which expression levels of miR-29b, miR-34a and miR-155 were found to be increased while miR-181a and miR-181b decreased. However, there were no differences in the expression levels of miR-15a/miR-16-1 between CLL patients and healthy donors, but the expression levels of miR-15a/miR-16-1 in CLL patients with a 13q deletion was depressed. In addition, there was no difference in the expression level of the above 7 miRNAs between 44 Han and 40 Uygur CLL patients. The expression levels of miR-29b, miR-181a and miR-181b correlated with IGVH mutations, while the expression levels of miR-34a, miR-29b and miR-181b correlated with a p53 abnormality in 84 Uygur and Han CLL patients. Taking p53 abnormality as the cut-off value criteria, low expression levels of miR-34a (cut-off value 4.65, P  = 0.02) and miR-29b (cut-off value 4.71, P  = 0.009) hinted at a poor treatment-free survival (TFS) prognosis for all CLL patients. Thus miR-34a and miR-29b may represent useful indicators for the prognosis of both Uygur and Han CLL patients. Highlights: 68 miRNAs were differentially expressed in CLL B lymphocytes. miR-15a/miR-16-1 exhibited no deregulation in Uygur CLL patients. miR-29b, miR-181a and miR-181b correlated with IGVH mutations. miR-34a, miR-29b and miR-181b correlated with p53 mutations. low miR-34a and miR-29b expression correlated with poor TFS.